2016
DOI: 10.1007/s00466-016-1348-1
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel model reduction for uncertainty quantification in computational structural dynamics

Abstract: This work deals with an extension of the reduced-order models (ROMs) that are classically constructed by modal analysis in linear structural dynamics of complex structures for which the computational models are assumed to be uncertain. Such an extension is based on a multilevel projection strategy consisting in introducing three reduced-order bases (ROBs) that are obtained by using a spatial filtering methodology of local displacements. This filtering involves global shape functions for the kinetic energy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…It is recalled that for the case false[double-struckWfalse]=false[double-struckMfalse], the residual kinetic energy, Ekfalse(trueu˙false)Ekrfalse(trueu˙false), is minimum, for all trueu˙ in RN. More precisely, for all truev˜ in subspace Sr, it can be shown that Ekfalse(trueu˙false)Ekfalse(trueu˙rfalse)=Ekfalse(trueu˙trueu˙rfalse)Ekfalse(trueu˙truev˜false). The expressions for matrices false[double-struckPfalse] and false[Mrfalse] and for product false[Mrfalse]trueu˙ are now given, for the case of weight matrix false[double-struckWfalse]=false[double-struckMfalse] and reduced basis [ B ] = [ T (0)]. It can be verified that the equality false[double-struckWfalse]=false[double-struckMfalse] implies low‐rank mass matrix false[Mrfalse] to be such that false[Mrfalse]=false[double-struckMfalse]false[double-struckPfalse].…”
Section: Second Methods Proposed: Construction Of a Global‐displacemenmentioning
confidence: 99%
See 3 more Smart Citations
“…It is recalled that for the case false[double-struckWfalse]=false[double-struckMfalse], the residual kinetic energy, Ekfalse(trueu˙false)Ekrfalse(trueu˙false), is minimum, for all trueu˙ in RN. More precisely, for all truev˜ in subspace Sr, it can be shown that Ekfalse(trueu˙false)Ekfalse(trueu˙rfalse)=Ekfalse(trueu˙trueu˙rfalse)Ekfalse(trueu˙truev˜false). The expressions for matrices false[double-struckPfalse] and false[Mrfalse] and for product false[Mrfalse]trueu˙ are now given, for the case of weight matrix false[double-struckWfalse]=false[double-struckMfalse] and reduced basis [ B ] = [ T (0)]. It can be verified that the equality false[double-struckWfalse]=false[double-struckMfalse] implies low‐rank mass matrix false[Mrfalse] to be such that false[Mrfalse]=false[double-struckMfalse]false[double-struckPfalse].…”
Section: Second Methods Proposed: Construction Of a Global‐displacemenmentioning
confidence: 99%
“…For all bolduRN, let u r denote the orthogonal projection of u onto subspace Sr. It is given by ur=false[double-struckPfalse]boldu, in which the orthogonal‐projection matrix false[double-struckPfalse] is an ( N × N ) real matrix that can be written as false[double-struckPfalse]=false[Bfalse]()false[Bfalse]Tfalse[double-struckWfalse]false[Bfalse]1false[Bfalse]Tfalse[double-struckWfalse]. On the other hand, the kinetic energy Ekfalse(trueu˙false) associated with any time‐dependent velocity vector trueu˙ is given by Ekfalse(trueu˙false)=1false/20.1emtrueu˙Tfalse[double-struckMfalse]trueu˙. The kinetic energy Ekrfalse(trueu˙false)=Ekfalse(trueu˙rfalse) associated with the orthogonal projection trueu˙r=false[double-struckPfalse]trueu˙ of trueu˙ is given by Ekrfalse(trueu˙false)=1false/20.1emfalse(trueu˙rfalse)Tfalse[double-struckMfalse]trueu˙r=1false/20.1emtrue…”
Section: Second Methods Proposed: Construction Of a Global‐displacemenmentioning
confidence: 99%
See 2 more Smart Citations
“…The stochastic Helmholtz boundary value problem is also considered. We refer to [28] for Uncertainty Quantification for frequency responses in vibroacoustics, to [8,20,21] for model order reduction for random frequency responses in structural dynamics, and to [15,30] for the stochastic Helmholtz equation with uncertainty arising either in the forcing term or in the boundary data or in the shape of the scatterer.…”
Section: Introductionmentioning
confidence: 99%